1999
DOI: 10.1002/(sici)1521-3765(19990903)5:9<2566::aid-chem2566>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination Chemistry of the CF Group of Fluorocarbons: Thermodynamic Data and Ab Initio Calculations on CF-Metal Ion Interactions

Abstract: (26-fluoro-4,7,13,16-tetraoxa-1,10-diaza-tricyclo[8.8.7.1,20,24]hexacosa-20,22,24(26)-triene and 4,7,13,16-tetraoxa-1,10-diazatricyclo[8.8.7.1,20,24]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
(46 reference statements)
2
15
1
1
Order By: Relevance
“…Reflecting their coordination to a metal center, each of these C-F bonds are elongated by a small but significant distance (avg. 0.025 Å) relative to their corresponding unbound C-F bonds, a phenomenon that has been predicted computationally 22 and observed in other systems with C-F … Li interactions evident in the solid-state. 15,16…”
Section: Introductionsupporting
confidence: 63%
“…Reflecting their coordination to a metal center, each of these C-F bonds are elongated by a small but significant distance (avg. 0.025 Å) relative to their corresponding unbound C-F bonds, a phenomenon that has been predicted computationally 22 and observed in other systems with C-F … Li interactions evident in the solid-state. 15,16…”
Section: Introductionsupporting
confidence: 63%
“…Examples of fluorocarbon coordination are known for metals in every block (s, p, d, f) of the periodic system 4. The RF→M interaction is, in general, weak,6 but may exert a distinct stabilizing or protective effect,7 often influencing the activity of some metal‐based catalytic systems 7b. Interestingly, Schelter and co‐workers have recently found that RF→M interactions (Scheme ; X=H, F) can also forge the coordination sphere of f elements, thereby enabling quite unusual geometries 8…”
Section: Methodsmentioning
confidence: 99%
“…The interaction between the alkali-metal ion and the fluorine atom might favor the leaving of fluoride in the ipso-selective defluorinative amination step. 27 Importantly, the success of this reaction arises from the different bond energies of the sequentially cleaved C(sp 3 )-F bonds, which enables the sequential ipso-/γ-selective defluorinative amination process of the reaction pathway. The different priority of the amine nucleophiles involved in these two different steps enables the distinguishing of the two amines.…”
Section: Resultsmentioning
confidence: 99%